Impact of the vegan diet on sperm quality and sperm oxidative stress values: A preliminary study - Marija Kljajic; Mohamad Eid Hammadeh; Gudrun Wagenpfeil; Simona Baus; Panagiotis Sklavounos; Erich-Franz Solomayer; Mariz Kasoha (Wolters Kluwer Medknow Publications, 2021)
Background: Insufficient nutrition and inappropriate diet have been related to many diseases. Although the literature confirms the hypothesis that particular nutritional factors can influence the quality of semen, until today, there are no specific dietary recommendations created for infertile males. Since the male contribution to the fertility of a couple is crucial, it is of high importance to determine the dietary factors that can affect male fertility. Aim: The aim of the present study was to evaluate differences in sperm quality parameters, sperm oxidative stress values and sperm acrosome reaction between vegan diet consumers and non-vegans. Setting and Design: Prospective study in a University Medical School. Materials and Methods: The present study was undertaken to evaluate the sperm quality parameters of vegan diet consumers (10 males who had a strictly vegetable diet with no animal products) and compare them with non-vegans (10 males with no diet restrictions). Semen quality was assessed following the World Health Organization (2010) criteria. Acrosome and DNA integrity has been evaluated using the immunofluorescence technique. Statistical Analysis: All variables were analysed by IBM SPSS version 24. Mean differences among groups were compared by Mann-Whitney U-test. Results: Obtained results showed that total sperm count (224.7 [117-369] vs. 119.7 [64.8-442.8]; P = 0.011) and the percentage of rapid progressively motile sperm were significantly higher in the vegan group compared with the non-vegan group (1 [0-7] vs. 17.5 [15-30]; P < 0.0001). Furthermore, the oxidation-reduction potential (0.4 [0.3-0.9] vs. 1.5 [0.6-2.8]; P < 0.0001) and the proportion of spermatozoon with DNA damage (14.7 [7-33.5] vs. 8.2 [3-19.5]; P = 0.05) were significantly higher in the non-vegan group in comparison to the vegan group. Conclusions: Results obtained in this study provide additional evidence about the favourable effect of a plant-based diet on sperm parameters. To confirm our preliminary findings, further studies including larger cohorts are warranted.